Long-term Outcomes of Deep Anterior Lamellar Keratoplasty in Macular Corneal Dystrophy—A Retrospective Analysis - Shreesha K. Kodavoor; Tasneem Neemuchwala; Ramamurthy Dandapani (TNOA Journal of Ophthalmic Science and Research, 2024)
Purpose: To study the long-term outcomes and complications in patients who underwent deep anterior lamellar keratoplasty (DALK) for macular corneal dystrophy (MCD). Methods: This is a retrospective analysis of all patients who underwent DALK in a tertiary eye care hospital in South India from 2011 to 2020. A total of 51 eyes of 33 patients were evaluated. All eyes underwent successful DALK by big bubble technique (32 eyes) or layer-by-layer dissection (19 eyes). Patients were followed up for 18 months to 9 years. Results: There was a significant improvement in vision (uncorrected and best-corrected visual acuity) post-DALK. The best corrected visual acuity after surgery was 0.3 logMAR (20/40) or better in 66.7% of operated eyes. Complications noted during surgery were intra-operative perforation. Post-operative complications include double AC, cataract, raised intraocular pressure, interface vessels and recurrence of the dystrophy. Conclusion: DALK is a safe and viable procedure for MCD management and gives good visual outcomes.